Diagnostic accuracy of hematoxylin-eosin staining in comparison to calretinin and S100 for the assessment of ganglion cells in rectal biopsy - Aziz, Zainab Waleed Aziz; Al Hajjar, Bassam Khalid; Al Hajjar, Ziyad Ahmed Abed; Almola, Ehsan Mahmood Abdullah; Jawher, Nazar Mohammed Taher; Muhammad, Radhwan Khudhur Muhammad (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess the diagnostic accuracy of haematoxylin-eosin staining in clinically suspected Hirschsprung disease, and to compare the findings with calretinin and S100 immunohistochemistry. Method: The retrospective study was conducted at the AL-Khansaa Teaching Hospital, Nineveh, Iraq, and comprised data from January 2017 to October 2020 of rectal suction biopsies of patients with clinically and radiologically suspected Hirschsprung disease. Histopathology and immunohistochemistry were performed. Data was analysed using SPSS 16. —Continue